Atypical Imaging Appearances of First Branchial Cleft Anomalies: Two Pathologically Proven First Branchial Cleft Anomalies Containing Fat on Imaging - Akash Meesa; Priyanka Meesa; Indu Rekha Meesa; Suresh K Mukherji (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Branchial anomalies (BA) are developmental lesions that are believed to be either vestigial remnants resulting from incomplete obliteration of the branchial apparatus or the result of buried epithelial cell rests. They are classified as either first, second, third, or fourth according to their proposed pouch or cleft of origin and are relatively common findings. The incidence of BAs depends on the age of the patient and the specific type of anomaly. Some anomalies might be very small and not present until they become symptomatic from an inciting event such as infection or trauma. Most radiologists are familiar with the classic findings of the most common forms of 1st and 2nd BAs. However, some BAs can have a varied imaging appearance and may be misdiagnosed. In this paper, we present two cases of pathologically proven first branchial cleft anomalies with atypical imaging appearances.